Ratio and index of Neurofilament light chain indicate its origin in Guillain‐Barré Syndrome. Issue 11 (8th October 2020) - Körtvelyessy, Peter; Kuhle, Jens; Düzel, Emrah; Vielhaber, Stefan; Schmidt, Christian; Heinius, Annika; Leypoldt, Frank; Schraven, Burkhart; Reinhold, Dirk; Leppert, David; Goihl, Alexander
Abstract: Objective: Neurofilament light chain (NfL) has been established as a biomarker of axonal damage in many diseases of the central nervous system (CNS). Increased levels of serum NfL (sNfL) can derive as well from damage in the peripheral nervous system (PNS) as from CNS, but little is known about the quantities contributing to sNfL. Peripheral nerve damage may be reflected by an increase in sNfL levels, while the NfL CSF/serum ratio and NfL index decreases. Methods: We collected serum and cerebrospinal fluid (CSF) from 21 Guillain‐Barré Syndrome (GBS) patients and measured NfL in serum and CSF and compared them with 19 neurologically healthy controls. Results: In general, NfL in CSF and serum was significantly higher in GBS patients. Serum NfL was higher in GBS patients admitted to the intensive care unit ( P = 0.02). Controls had a mean CSF/serum NfL ratio of 26.7 (ranging from 5.8 to 69.5) indicating a central origin of NfL. Three GBS patients had a similar range (23.9 to 42.7, mean 33.3) all of them with demyelinating pathology in the PNS. Eighteen GBS patients with axonal or mixed axonal‐demyelinating pathology showed significantly lower CSF/serum ratios (0.02–12.2, mean 4.4), indicative of a peripheral origin of NfL. When applying the NfL index subdivisions remain the same. Interpretation: These results demonstrate that the PNS is a relevant contributor to sNfL levels and that the distribution can be identified by a lowered NfL CSF/serum ratio of NfL index. Furthermore, acute or subacute polyneuropathies are likely confounding factors in interpreting sNfL levels in CNS diseases.